Assessment of pollution dispersion from Gebeng industrial area - Gimbun, Jolius (2017)
Air pollution dispersion is greatly affected by the wind speed and direction. Most often the pollution dispersion from industrial area is not fully understood. In the present work, the effect of surface topology on the wind speed and atmospheric turbulent around the Gebeng industrial area in Pahang was studied using a computational fluid dynamics (CFD) method. The typical southeastern wind with a speed of about 1.3003 m/s corresponding to the actual speed of approximately 5 km/h was considered for validation. The turbulent flow was modelled using k-ε model. The model was compared with the laser Doppler velocimetry (LDV) measurement on the scale-down rig. The CFD prediction showed good agreement within 10% deviation with the experimental measurement via LDV. It was found that the plume of noxious gas driven by the eastern wind can affect the nearby residential area R2, whereas the western wind is affecting the residential area R1. In the presence of hill obstacle, the gas plume moves southward into the flat terrain. In addition to the CFD simulation, gas dispersion analysis using ALOHA software is also studied. The chlorine dispersion was modelled using the heavy gas cloud model and the incident zone area is plotted accurately from the point of release with the aid of GPS coordinate and google map. The risk zone and the affected residential area were identified and the safety evacuation route in the event of accidental chlorine leak is also suggested. Results from this work may be useful to understand the risk of air pollutant dispersion around Gebeng industrial area.